The first biological choice in patients with rheumatoid arthritis: data from the Moroccan register of biotherapies - Eddaoudi, Meryem (Pan Afr Med J, 2021)
INTRODUCTION: the aim of our study is to determine, from data of the Moroccan register of biotherapies, the factors influencing the choice of the first prescribed biological treatment. METHODS: cross-sectional multicenter study including rheumatoid arthritis patients who were initiated the first biological treatment either: Rituximab, an anti-TNF, or Tocilizumab. The determinants related to the patient and disease have been gathered. A univariate and then multivariate analysis to determine the factors associated with the choice of the first bDMARDs was realized. RESULTS: a total of 225 rheumatoid arthritis patients were included in the Moroccan registry. The mean age was 52 ± 11 years, with female predominance 88% (n = 197). The first prescribed biological treatment was Rituximab 74% (n = 166), the second one was Tocilizumab, 13.6% (n = 31) then comes the anti-TNF in 3(rd) position with 12.4% (n = 28). The factors associated with the choice of Rituximab as the first line bDMARDs prescribed in univariate analysis were: the insurance type, the positivity of the rheumatoid factor. In multivariate analysis, only the insurance type that remains associated with the choice of Rituximab as the first biological drugs. The Tocilizumab was associated with shorter disease duration and was more prescribed as mono-therapy compared to non Tocilizumab group. TNFi was associated with the insurance type. CONCLUSION: our study suggests that Rituximab and TNFi are associated with the type of insurance and Tocilizumab is the most prescribed biologic mono-therapy in RA patients. Further studies are needed to confirm these results.